1999
DOI: 10.1515/jpm.1999.031
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and neonatal outcome of twin pregnancies complicated by single fetal death

Abstract: Expectant management of single fetal death in twin pregnancies might be advisible under close surveillance of both, mother and the surviving fetus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
1
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 16 publications
2
21
1
2
Order By: Relevance
“…The chorionicity rather than zygosity determines the outcome (Bajoria et al, 1999;Caroll et al, 2002;Stenhouse et al, 2002). Single fetal death at 20 weeks' gestation or more were uncommon in twin pregnancies (Axt et al, 1999). In our study the incidence of single fetal death was 3.3% which is consistent with the recent findings.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The chorionicity rather than zygosity determines the outcome (Bajoria et al, 1999;Caroll et al, 2002;Stenhouse et al, 2002). Single fetal death at 20 weeks' gestation or more were uncommon in twin pregnancies (Axt et al, 1999). In our study the incidence of single fetal death was 3.3% which is consistent with the recent findings.…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies showed that close monitoring for maternal coagulopathy in pregnancies complicated with single fetal death is not compulsory. While some authors have reported high incidence of preeclampsia, only three women (9.4%) had preeclampsia in our series (Axt et al, 1999;Santema et al, 1995). In multiple pregnancies, the effect of the timing of an intrauterine death on the outcome of the surviving co-twin is still controversial.…”
Section: Twin Research February 2004contrasting
confidence: 53%
“…36 In this systematic review, where there was comparative data within studies, there were only two deaths and one case of neurological injury in known dichorionic twins. It is clear from this review that data has thus far been poorly reported and that this area needs further robust Monochorionic n = 19 n = 4 n = 50 n = 8 n = 8 n = 6 n = 12 n = 12 n = 7 n = 4 n = 5 n = 13 n = 7 n = 5 n = 4 n = 21 n = 8 n = 6 n = 5 n = 9 n = 8 n = 7 n = 4 n = 14 n = 3 n = 33 n = 11 n = 6 n = 2 n = 3 n = 3 n = 6 n = 10 n = 1 n = 9 n = 9 n = 3 n = 7 n = 5 n = 9 n = 7 n = 5 n = 17 n = 4 n = 11 n = 7 n = 2 n = 4 n = 16 n = 3 n = 42 n = 11 n = 8 n = 2 n = 3 n = 13 n = 7 n = 7 n = 181 n = 47 n = 16 n = 9 n = 1 Abdal-khalig and Sobande 33 Axt et al 10 Bajoria et al 12 Eglowstein and D'Alton 30 Fusi and Gordon 21 Gaucherand et al 26 Ishimatsu et al 32 Jou et al 29 Kilby et al 15 Malinowski et al 9 Petersen and Nyholm 16 Santema et al 19 Sonneveld and Correy 31 Woo et al…”
Section: Discussionmentioning
confidence: 99%
“…Abdal-khalig and Sobande 33 Axt et al 10 Bajoria et al 12 Eglowstein and D'Alton 30 Fusi and Gordon 21 Gaucherand et al 26 Ishimatsu et al 32 Kilby et al 15 Malinowski et al 9 Petersen and Nyholm 16 Pharoah and Adi 1 Rydhstrom 28 Santema et al 19 Sonneveld and Correy 31 Woo et al …”
mentioning
confidence: 99%
See 1 more Smart Citation